A study on risk factors associated with neonatal hyperbilirubinemia among newborns at tertiary care level in Kerala, India - S., Chandramohan Reddy; Varghese, Sam (International Journal of Contemporary Pediatrics, 2020)
Background: Neonatal hyperbilirubinemia is defined as serum bilirubin levels >7 mg/dl around 85% of all term newborns and most of the premature babies develop clinical jaundice and various associated risk factors are involved in NNH and treatment for this condition depends on gestational age, serum bilirubin levels at different time interval during early life of these newborns and treating them with phototherapy or exchange transfusion. Objective of the study was to establish the relation with the NNH and risk factors among newborns and treatment with the phototherapy if required. Methods: The present prospective study was conducted at Karuna Medical College, Chittur Palakkad from January 2019 to December 2019. A total of 40 samples which are born during the study period were included in the study. All types of gestations (preterm, full term, post term), both genders (male and female), new-borns with risk factors, serum bilirubin (TSB) >7 mg/dl at 48 hrs of life were included in the study Results: In our study, female samples consists of 55% and male samples were 45% during the study period minimum gestational age was 35 weeks and maximum was 40 weeks. 5% sample with a serum bilirubin level of 9 mg/dl, with risk factor as a Rh(-ve) incompatibility was treated with phototherapy up to 96 hrs of life. Conclusions: Study conveys various risk factors responsible for NNH and treatment with phototherapy given to the affected new-borns. With good clinical history, risk factors involved in new-borns, antenatal counseling is needed to all pregnant women’s it is necessary to check the serum bilirubin levels and treated with phototherapy to avoid further NNH related complications in the new-borns.